TEACHER PROFESSIONAL DEVELOPMENT THROUGH ENGLISH TEACHER WORKING GROUP (MGMP) - SILFI SANDA (Sriwijaya University Learning and Education International Conference, 2016)
skills of a teacher. The role of MGMP in improving the teacher’s professionalism is becoming moreimportant when the government is implementing new curriculum. This research aims at finding outthe role of English Teacher Working Group (MGMP Bahasa Inggris) to Support TeacherProfessionalism Development to Senior High Schools in Kabupaten OKU in the academic year of2015/2016. The population was the English teachers of SMA, students, the board of management ofEnglish MGMP of Senior High School, and Vice Principles of Curriculum from State Senior HighSchool in Kabupaten OKU. The research was a descriptive qualitative by using purposive sampling.Techniques of data collection were done through in-depth interviews, direct observation, documentanalysis. Data analysis technique was in form of interactive analysis techniques. Further data havebeen obtained used by triangulation method to obtain truly valid data. Based on research data analysisit can be concluded that; (1) English MGMP for Senior High School in Kabupaten OKU contributegreatly to the development of Senior High School English teacher professionalism in Kabupaten OKUin terms of developing the syllabus, annual and semester program, and lesson plan, developingteaching method and the innovative learning model, developing the use of teaching media and theevaluation system and improving the teachers professional competence; (2) English MGMP inKabupaten OKU still found obstacles in its implementation so that it is needed for solving theproblems in order the activities of English MGMP run better for the following years.